2010
DOI: 10.1111/j.1365-2516.2010.02233.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable region heavy chain glycosylation determines the anticoagulant activity of a factor VIII antibody

Abstract: Summary. The mechanism of action of antibodies inhibiting partially factor VIII (FVIII) activity (type II inhibitor) is still poorly understood. We produced an unusual type II monoclonal antibody, called LE2E9, derived from a patient with mild haemophilia A. The antibody displayed several unexpected structural and functional properties such as glycosylation in the variable region, binding to the FVIII C1 domain, inhibition of maximum 80-90% FVIII activity when in excess over FVIII, and prevention of FVIII bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…However, molecular dynamic simulations suggest that some attached N-glycans may modulate PrP C stability (128,139,598), although experimental evidence is still lacking (213). Nevertheless, protein glycosylation affects other protein properties, such as intracellular traffic and ligand binding (299,413,504), the latter of which may be modulated both by subtle effects on protein structure as well as by steric hindrance (32,70,237,243,393,513). Indeed, glycosylation reportedly affects the recognition of various species of PrP C by monoclonal antibodies in both the brain and in other cells (27,289), and differing responses to certain monoclonal antibodies were described for cells bearing distinctly glycosylated forms of PrP C (365).…”
Section: A Structure Of Prp Cmentioning
confidence: 99%
“…However, molecular dynamic simulations suggest that some attached N-glycans may modulate PrP C stability (128,139,598), although experimental evidence is still lacking (213). Nevertheless, protein glycosylation affects other protein properties, such as intracellular traffic and ligand binding (299,413,504), the latter of which may be modulated both by subtle effects on protein structure as well as by steric hindrance (32,70,237,243,393,513). Indeed, glycosylation reportedly affects the recognition of various species of PrP C by monoclonal antibodies in both the brain and in other cells (27,289), and differing responses to certain monoclonal antibodies were described for cells bearing distinctly glycosylated forms of PrP C (365).…”
Section: A Structure Of Prp Cmentioning
confidence: 99%
“…In most of the IgGs, mutations abrogating the glycosylation of the V region resulted in a significant decrease in their binding affinity for the target antigen 34 . Another study demonstrated that a human IgG alloantibody (LE2E9) that neutralizes the pro-coagulant activity of factor VIII, has a complex glycan structure bound to CDR H1 38 . While the removal of the V-linked glycan by mutagenesis did not affect the antibody's binding affinity for factor VIII, it significantly decreased its neutralizing activity.…”
Section: Structural Analyses Of the Cd4i Monoclonal Antibodies 47e Ementioning
confidence: 99%
“…Moreover, although the wild-type LE2E9 antibody efficiently blocked the binding of factor VIII to its chaperone -von Willebrand factor -the aglycosylated LE2E9 antibody lost this activity. This suggests that the glycan in the LE2E9 antibody blocks the interaction of factor VIII with von Willebrand factor through steric hindrance 38 . These findings point to the importance of V region glycans for modulating the functional activity of antibodies independently of the antigen-binding properties of the antibody.…”
Section: Structural Analyses Of the Cd4i Monoclonal Antibodies 47e Ementioning
confidence: 99%
“…TB‐402 is a human IgG4 antibody that in vitro exerts a plateau inhibition of factor (F)VIII activity even when TB‐402 is in large excess over FVIII [3]. In vivo, increasing the dose prolongs its pharmacodynamic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The antithrombotic efficacy of TB‐402 has been evaluated in a thrombotic priapism model in mice with type II heparin‐binding site antithrombin deficiency [3]. TB‐402 prevented the development of microscopic and macroscopic thrombus in all mice tested.…”
Section: Introductionmentioning
confidence: 99%